Applying urban parametric design optimisation processes to a hot climate: Case study of the UAE - Taleb, Hanan (2014)
Parametric and algorithmic design is considered a current trend in architectural design processes. In recent times architects and designers have gained control over the design process by using parametric design to produce an original sustainable design that interacts with the project's environment, climatic and sustainable constraints. Research into parametric urban design shows it to be a good tool for achieving sustainable and healthy communities. It does this through minimum form and high performance spaces, particularly in hot climatic zones where outdoor life is absent, there is an abundance of solar radiation, and local materials and resources are rare or limited. Consequently, the aim of this research paper is to investigate the potential for applying parametric design optimisation processes over conventional urban design processes in order to achieve a more sustainable style of urban design. The methodology adopted for this study is the use of current state-of-the-art computer tools like Grasshopper and ANSYS CFX to achieve optimised parametric design. An urban area in Dubai was selected to act as the case study location for this project. An in-depth analysis was carried out between the base case and the optimised case. Future recommendations were drawn based on the findings and results. The study covered many environmental factors such as solar irradiation, urban ventilation, building form and orientation to achieve the optimum sustainable urban morphology.